Antioxidant Activities of The Extracts of Carya cathayensis Sarg. - Liu, Yuan-Hui; Lv, Jie-Li; Yuan, Ke; Yang, Ping (Asian Journal of Chemistry, 2010)
With the Carya cathayensis Sarg. produced in Lin'an, Zhejiang Province as the research object,Caryaextracts of epicarp (CCEE), Carya cathayensis Sarg. extracts of leaf (CCEL)Carya cathayensis Sarg. extracts of tegument (CCET). On this basis, we also researchedCarya cathayensis Sarg., 20 % methanol enrichmentCarya cathayensis Sarg. extracts of epicarp (20 % MEF-CSEE), 40 % methanolCarya cathayensis Sarg. extracts of epicarp (40 %MEF-CSEE), 60 %Carya cathayensis Sarg. extracts of epicarp (60 % MEF-CSEE) Carya cathayensis Sarg. the 40 % MEF-CSEE contains the highest amount of total phenolics, the 20 % MEF-CSEE contains the highest amount of total flavonoids. Through the research of antioxidant activity we know that all the parts of the ethanol extracts in the scavenging free radicals, among which the antioxidant activity in the 40 % MEF-CSEE part is the strongest. Here, the main components of antioxidant activity should be the flavonoids and the phenolic components and we further know that there is a direct relationship between contents of the flavonoids and the phenolic and the antioxidant activity. The exocarp of cathayensis Sarg of antioxidants.The experiment result provided a scientific basis for the further development of its medical effects and the research for the tegument. all contain the flavonoids and the phenolic component, among whichCarya cathayensis Sarg. have the effect ofCaryais a under utilized resource, It might be considered as a potential plant sourceCarya cathayensis Sarg. epicarp, its leaf and the this paper determined the content of the total flavonoids and the total phenolic in the cathayensis Sarg. and the the ethanol extracts in different part of the fraction of enrichment fraction of methanol enrichment fraction of on DPPH radicals scavenging effect. The experiment result shows that the different part of the